PERBANDINGAN METODE TOPSIS DAN SAW PADA SISTEM PENDUKUNG KEPUTUSAN PENENTUAN MUSTAHIK : INDONESIA - Ade Nur Kurnia Rizqi Ananda (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Abstract- LAZISMU is an amil zakat institution that has an obligation to empower the community which has the goal of achieving community relief from poverty. For economic empowerment, sometimes there are some obstacles in the delivery, such as the lack of precise targeting and not even all those who apply for assistance, so the author of Art conducts research for the decision-making system in selecting mustahiq using several comparisons such as the TOPSIS and SAW methods. It is hoped that this research can facilitate field programs in shopping for mustahiq who are suitable for getting assistance, which should be prioritized first. the TOPSIS method with the first alternative produces a value of 0.5884 which is set as the first choice. Whereas the SAW method with the first alternative result of 0.7133 is set as the main choice. From all the calculations and the results of the ranking values ​​that have been obtained, the SAW method is much more recommended for mustahiq hairdressers compared to the TOPSIS method because the results obtained from considering this method are far greater than the SAW method compared to the TOPSIS method